Comparing simple and functional jejunal interposition with preserved duodenal passage after total gastrectomy - Xue-Lu Zhou; Yan-Qing Deng; Pei-Jie Zhang; Hai Huang; Huan-Bin Zhang; Hong-Shuai Li; You-Hua Wang; Jian-Hua Luo (Asian Journal of Surgery)
Objective: This prospective randomized controlled trial aimed to compare the effectiveness of functional jejunal interposition (FJI) and simple jejunal interposition (SJI) as reconstruction methods following total gastrectomy for gastric cancer. The study assessed primary endpoints such as nutritional status and quality of life, as well as secondary endpoints including operative time, intraoperative blood loss, perioperative and postoperative complications, and survival rate. Methods: A total of 113 patients were randomly assigned to either the FJI group or the SJI group. Surgical procedures were performed according to the allocated group. Nutritional status was evaluated based on plasma nutritional parameters, weight loss, and the nutritional assessment index (NAI). Quality of life was assessed using Cuschieri scores and Visick scores. Operative time, intraoperative blood loss, perioperative and postoperative complications, and survival rate were also recorded. Results: There were no significant differences observed between the FJI group and the SJI group in terms of primary and secondary endpoints. Both groups showed similar outcomes in terms of nutritional status, quality of life, perioperative and postoperative complications, and survival rate. The operative time was longer in the FJI group compared to the SJI group. Conclusion: This study shows that both FJI and SJI are effective at maintaining nutrition, quality of life, and survival rate after total gastrectomy for gastric cancer. Although FJI is more complex, SJI is preferred due to its shorter duration. Surgeons should choose the most appropriate method based on the patient's characteristics and their own skills.